CLIMATE CHANGE AS A RISK FACTOR FOR ACUTE EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Editora Impacto Científico, 2025)
Climate change is one of the greatest public health challenges of the 21st century, directly impacting the morbidity and mortality of chronic diseases such as Chronic Obstructive Pulmonary Disease (COPD). Scientific evidence shows that extreme weather events, such as heat waves, abrupt temperature fluctuations, and increased air pollution, are associated with higher rates of acute exacerbations in COPD patients. These exacerbations not only impair patients’ quality of life but also overload healthcare systems, raising hospitalization and treatment costs. Furthermore, socioeconomically vulnerable populations are disproportionately affected by the adverse effects of climate change due to limited adaptive capacity and reduced access to adequate healthcare. In this context, it is essential to understand the mechanisms through which climatic factors influence COPD pathophysiology and to identify preventive strategies and public policies aimed at mitigating these risks. This chapter aims to analyze the relationship between climate change and acute COPD exacerbations, highlighting key environmental, social, and clinical risk factors. It also seeks to discuss adaptation measures in public health, ranging from epidemiological surveillance to the strengthening of primary healthcare, as strategies to minimize the negative impacts of this global phenomenon on respiratory populations.